Effect of indigenous mycorrhizal colonization on phosphorus-acquisition efficiency in soybean and sunflower - Fernández, Mariana Cecilia (2011)
Despite a general consent about the beneficial contribution of arbuscular mycorrhizal fungi (AMF) on natural ecosystems, there is an intense debate about their role in agricultural systems. In this work, soybean (Glycine max L.) and sunflower (Helianthus annuus L.) field plots with different P availabilities were sampled across the Pampean Region of Argentina (> 150 samples from Mollisols) to characterize the relationship between available soil P and indigenous mycorrhizal colonization. A subsequent pot experiment with soybean and sunflower was carried out to evaluate the effect of P supply (0, 12, and 52 mg Pkg -1) and AMF inoculation on AMF colonization and crop responsiveness to P in a Mollisol. Both crops showed high AMF colonization in the field (average: 55% for soybean and 44% for sunflower). While mycorrhizal colonization in soybean was significantly and negatively related to available soil P, no such trends were apparent in sunflower. Also, total biomass was 3.5 and 2.0 times higher in mycorrhizal than in nonmycorrhizal pot-grown soybean under low- and medium-P conditions, respectively. Sunflower, on the other hand, did not benefit from AMF symbiosis under medium and high P supply. While mycorrhization stimulated P-uptake efficiency in soybean, the generally high P efficiency in sunflower was not associated with AMF symbiosis.